How Sustained Is 24-Hour Diffusion-Weighted Imaging Lesion Reversal?: Serial Magnetic Resonance Imaging in a Patient Cohort Thrombolyzed Within 4.5 Hours of Stroke Onset. Issue 3 (March 2015) - Soize, Sebastien; Tisserand, Marie; Charron, Sylvain; Turc, Guillaume; Ben Hassen, Wagih; Labeyrie, Marc-Antoine; Legrand, Laurence; Mas, Jean-Louis; Pierot, Laurent; Meder, Jean-François; Baron, Jean-Claude; Oppenheim, Catherine
Abstract : Background and Purpose—: Here, we assessed how sustained is reversal of the acute diffusion lesion (RAD) observed 24 hours after intravenous thrombolysis, and the relationships between RAD fate and early neurological improvement. Methods—: We analyzed 155 consecutive patients thrombolyzed intravenously 152 minutes (median) after stroke onset and who underwent 3 MR sessions: 1 before and 2 after treatment (median times from onset, 25.6 and 54.3 hours, respectively). Using voxel-based analysis of diffusion-weighted imaging (DWI)1, DWI2, and DWI3 lesions on coregistered image data sets, we assessed the outcome of RAD voxels (hyperintense on DWI1 but not on DWI2 ) as transient or sustained on DWI3, and their relationships with early neurological improvement, defined as ΔNational Institutes of Health Stroke Scale ≥8 or National Institutes of Health Stroke Scale ⩽1 at 24 hours. T max and apparent diffusion coefficient values were compared between sustained and transient RAD voxels. Results—: The median (interquartile range) baseline National Institutes of Health Stroke Scale and DWI1 lesion volume were 11 (7–18) mL and 15.6 (6.0–50.9) mL, respectively. The median (interquartile range) RAD volume on DWI2 was 2.8 (1.1–6.6) mL, of which 70% was sustained on DWI3 . Sixteen (10.3%) patients had sustained RAD ≥10 mL. As compared with transient RAD voxels, sustained RAD voxels had nonsignificantly higher baseline apparent diffusion coefficient values (median [interquartile range], 793 [717–887] versus 777 [705–869]×10 −6 mm 2 ·s −1, respectively; P =0.08) and significantly better perfusion ( T max, mean±SD, 6.3±3.2 versus 7.8±4.0 s; P <0.001). At variance with transient RAD, the volume of sustained RAD was associated with early neurological improvement in multivariate analysis (odds ratio, 1.08; 95% confidence interval, [1.01–1.17], per 1-mL increase; P =0.03). Conclusions—: After thrombolysis, over two-thirds of the DWI lesion reversal captured on 24-hour follow-up MR is sustained. Sustained DWI lesion reversal volume is a strong imaging correlate of early neurological improvement. Abstract : Supplemental Digital Content is available in the text.